Structural and functional analysis of the GRAS gene family in grapevine indicates a role of GRAS proteins in the control of development and stress responses - Jerome eGrimplet; Patricia eAgudelo Romero; Rita eTeixeira; Jose Miguel Martinez Zapater; Ana Margarida Fortes (Frontiers in Plant Science, 2016)
GRAS transcription factors are involved in many processes of plant growth and development (e.g. axillary shoot meristem formation, root radial patterning, nodule morphogenesis, arbuscular development) as well as in plant disease resistance and abiotic stress responses. However, little information is available concerning this gene family in grapevine (Vitis vinifera L.), an economically important woody crop. We performed a model curation of GRAS genes identified in the latest genome annotation leading to the identification of 52 genes. Gene models were improved and three new genes were identified that could be grapevine- or woody-plant specific. Phylogenetic analysis showed that GRAS genes could be classified into 13 groups that mapped on the 19 Vitis vinifera chromosomes. Five new subfamilies, previously not characterized in other species, were identified. Multiple sequence alignment showed typical GRAS domain in the proteins and new motifs were also described. As observed in other species, both segmental and tandem duplications contributed significantly to the expansion and evolution of the GRAS gene family in grapevine. Expression patterns across a variety of tissues and upon abiotic and biotic conditions revealed possible divergent functions of GRAS genes in grapevine development and stress responses. By comparing the information available for tomato and grapevine GRAS genes, we identified candidate genes that might constitute conserved transcriptional regulators of both climacteric and non-climacteric fruit ripening. Altogether this study provides valuable information and robust candidate genes for future functional analysis aiming at improving the quality of fleshy fruits.